An equation of the form \(\displaystyle{y}={a}\cdot{b}^{{x}}\) represent exponential growth when b>1 and represents exponential decay when b

\(\displaystyle{y}={\left(\frac{{{3}^{{x}}}}{{{2}^{{x}}}}\right)}={\left(\frac{{3}}{{2}}\right)}^{{x}}\)

Since \(\displaystyle\frac{{3}}{{2}}{>}{1},{y}={\left(\frac{{{3}^{{x}}}}{{{2}^{{x}}}}\right)}={\left(\frac{{3}}{{2}}\right)}^{{x}}\) represent exponential growth.

\(\displaystyle{y}={\left(\frac{{{3}^{{x}}}}{{{2}^{{x}}}}\right)}={\left(\frac{{3}}{{2}}\right)}^{{x}}\)

Since \(\displaystyle\frac{{3}}{{2}}{>}{1},{y}={\left(\frac{{{3}^{{x}}}}{{{2}^{{x}}}}\right)}={\left(\frac{{3}}{{2}}\right)}^{{x}}\) represent exponential growth.